Health at older ages : the causes and consequences of declining disability among the elderly - Cutler, David M.; Wise, David A. (National Bureau of Economic Research conference report., 2008)
Americans are living longer--and staying healthier longer--than ever before. Despite the rapid disappearance of pensions and health care benefits for retirees, older people are healthier and better off than they were twenty years ago. In Health at Older Ages, a distinguished team of economists analyzes the foundations of disability decline, quantifies this phenomenon in economic terms, and proposes what might be done to accelerate future improvements in the health of our most elderly populations. This breakthrough volume argues that educational attainment, high socioeconomic status, an older ret.